Otogenic Intracranial Complications in Bir Hospital; an Eight Years Retrospective Review - Yadav, Lal Kishor; Thapa, Prakash bahadur; Pradhananga, jayendra (Nepalese Journal of ENT Head and Neck Surgery, 2018)
Objectives: To review our experiences on intracranial complications secondary to otitis media and to compare the results with other studies.Material and Methods: A retrospective chart review of  all patients with intracranial complications secondary to otitis media over eight years period in Bir hospital was done. Clinical presentation, radiological findings, microbiology, surgical management and antibiotics used were studied.Results: Forty eight cases were included in this study of which 23 had meningitis, 15 had brain abscess, 7 had lateral sinus thrombosis and 3 had petrositis. 37 of these were secondary to chronic otitis media and 11 were secondary to acute otitis media. Otorrhoea, headache, earache, fever, vertigo and vomiting were the main symptoms. Staphylococcus aureus was the most common bacteria isolated followed by Pneumococcus, Haemophilus influenzae and Klebsiella.Conclusion: Early recognition, multi drug treatment with broad spectrum antibiotic and multi disciplinary approach are the mainstay of management of otogenic intracranial complications.Nepalese Journal of ENT Head and Neck Surgery, Vol. 6, No. 1, 2015